Covid-19 outbreak and beyond: Retrospect on the information content of registered short-time workers for GDP now- and forecasting - Sylvia Kaufmann (Swiss National Bank, Study Center Gerzensee, 2022)
We document whether a simple, univariate model for quarterly GDP growth is able to deliver forecasts in a crisis period like the Covid-19 pandemic, which may serve cross-checking forecasts obtained from elaborate and expert models used by forecasting institutions. We include shocks to the log number of short-time workers as timely available current-quarter indicator. Yearly GDP growth forecasts implied by quarterly forecasts serve cross-checking, in particular at the outbreak of the pandemic.
Keywords: C32; C53; E23; E27; 330; Bayesian analysis; Covid-19; pseudo real-time; ordinances; SECO; KOF